Transient CFD Analysis of Thermal Regenerator - Kanojia, Nikhil (Journal of Graphic Era University, 2023)
The goal of the work is to analyze the impact of various factors on the fixed bed regenerator’s thermal characteristics while also examining the regenerator’s thermal characteristics. The thermal parameters of the regenerator are affected by a number of factors, including Heat storage capacity, switching time, residence time, bed height/length, regenerator diameter, particle diameter, and gas flow direction. The current study examines each of these variables quantitatively. Understanding the thermal regenerator’s temperature and fluid flow variations CFD analysis is conducted. For the analysis, Ansys Fluent is a for-profit program.